2021
DOI: 10.3906/bot-2103-50
|View full text |Cite
|
Sign up to set email alerts
|

Applications of CRISPR/Cas9-based genome editing in the plant biology

Abstract: Clustered regularly interspaced short palindromic repeats/CRISPR-associated proteins (CRISPR/Cas) is an acquired immune system found in bacteria and archaea that can specifically silence or degrade a foreign single or double strand nucleic acid to protect it from infection. In recent years, the CRISPR/Cas9 system has rapidly been evolved into a genome editing technology, in which the Cas9 endonuclease can be targeted to specific DNA sequences by guide RNAs (gRNAs) that are easily programmable. Due to simplicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 109 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…CRISPR-Cas9-mediated gene-editing tools, including PE, have been widely applied in plant cells [ 24 ], to increase yield, regulate metabolites, improve stress resistance, etc. [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR-Cas9-mediated gene-editing tools, including PE, have been widely applied in plant cells [ 24 ], to increase yield, regulate metabolites, improve stress resistance, etc. [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Krishna et al [ 104 ] further highlight CRISPR/Cas9′s role in conferring molecular immunity against drought stress in tomato, underlining its effectiveness in bolstering plant resilience. The versatility of CRISPR/Cas9 is also evident in the research of Zheng et al [ 105 ], who demonstrated its application in enhancing stress resistance across different plant species, thereby showcasing its broad applicability in plant stress management. Moreover, Park et al [ 106 ] presented evidence of CRISPR/Cas9′s capability to improve both abiotic and biotic stress tolerance in rice, underscoring its potential as a comprehensive tool for enhancing plant resilience to a wide array of environmental challenges, including drought.…”
Section: Crispr-cas9 and Genome Editingmentioning
confidence: 98%
“…Scope of CRISPR In the field of plant biology, the initial application of CRISPR/Cas9-based genome editing (Zheng et al, 2021). Demonstrated its extensive adaptability in the model species Arabidopsis and in the staple crop rice.…”
Section: Crispr/ Cas Genementioning
confidence: 99%